Interval walking training as a potential contributor to motor function improvement in adults with type 2 diabetes mellitus: a retrospective analysis - Yamazaki, Masanori; Hosokawa, Manami; Kitajima, Kohei; Komatsu, Mitsuhisa (Frontiers in Endocrinology, 2025)
AimIn adults with type 2 diabetes mellitus (T2DM), hyperglycemia and related complications may impair skeletal muscle mass (SMM) and quality, leading to reduced motor function. This study aimed to evaluate the effects of interval walking training (IWT) on three motor function indicators: peak vertical ground reaction force normalized by body weight (F/w), rate of force development normalized by body weight (RFD/w), and balance index score (BIS).MethodsThis retrospective analysis utilized data from a previous pilot trial of IWT. Changes in motor function were assessed using a motor function analyzer, and factors associated with these changes were identified using multiple linear regression analysis.ResultsAmong 51 adults with T2DM (including 24 aged ≥65 years), IWT significantly improved F/w (median [IQR]: 1.32 [1.26–1.36] to 1.32 [1.27–1.38] kgf/kg, p = 0.038), RFD/w (9.50 [8.03–13.12] to 10.2 [9.43–11.00] kgf/s/kg, p = 0.001), and BIS (52.0 [44.5–55.0] to 54.0 [48.0–56.0], p = 0.020). Notably, RFD/w showed significant improvement in both older (≥65 years: 9.45 [8.25–10.05] to 10.10 [8.80–10.45], p = 0.025) and non-older adults (<65 years: 9.90 [7.75–11.18] to 10.80 [9.58–11.85], p = 0.005). Baseline muscle quality was associated with changes in F/w and RFD/w, while increased leg SMM was linked to improvements in BIS.ConclusionsIWT may serve as a potential contributor to improved motor function in adults with T2DM, particularly when combined with strategies to maintain or enhance skeletal muscle quality and quantity.